Some Problems of Anti-recessionary Public Management in Russia at Present - Samarina, Vera P.; Skufina, Tatiana P.; Samarin, Aleksandr V.; Baranov, Sergey V. (International Review of Management and Marketing, 2016)
The most significant, in the author’s opinion, problems of anti-recessionary public management in Russia have been brought out in the article. The genesis of these problems having formed at present has been revealed. It has been shown that the whole complex of problems was generated with the change of the territorial approach to the public management. Some problems of public management of economic and political genesis have been formulated. A whole number of features of the system approach and its application to achievement of practical purposes of the anti-recessionary public management have been revealed. The feature of the system approach to the public management is that it is directed at the synthesis of the knowledge which is available in various fields of science. The approach purpose is seen in revealing of all complexes of separately taken interrelations of elements of state-management system with a society and development of complex anti-recessionary measures subject to the revealed interrelations. For the detection of economic efficiency of the Russian Federation activity the analysis of dynamics of a total gross domestic product of the country from 1991 up to date has been carried out.in the article. This period included some economic crises. The analysis has shown the inability of public authorities of Russia to react operatively to changing of environmental conditions. In reply to crisis calls public authorities of Russia more often implemented so-called “passive” anti-recessionary policy in which basis there was an expectation of crisis cessation on an international or state scales. Or it was so-called “half-hearted” anti-recessionary policy directed on some softening of crisis actions. In the article it is offered to reconsider basic approaches to the anti-recessionary public management. The author upholds the position that for successful development of the state only “active” anti-recessionary state policy based on maximum use of clearing and mobilizing features of crisis is possible. Only such anti-recessionary policy will promote a way out of the crisis not only with the minimum losses, but also with an acquired potential of development. It will reduce crisis vulnerability of the country in the period ahead. Keywords: anti-recessionary state policy, public management, system approach to the public management, genesis of problems, administrative-territorial system, Russian Federation JEL Classifications: D78, E01; H12; O47